Comparing book and its film version: The Hours - Krásný, Tomáš (Univerzita Pardubice, 2008)
Aim of the paper is to compare Michael Cunningham´s novel The Hours and its film version. The paper analyses the book and the film in terms of their plot, characters, themes and the differences betweeen each other. Since The Hours is based on Virginia Woolf´s Mrs. Dalloway, brief comparison of these novels is made. Furthermore, the period of Modernism is described with focus on Modernist writing and its techniques, such as stream of consciousness.
Srovnání knihy a její filmové verze: Hodiny
Keywords: Modernism; stream of consciousness; The Hours; Mrs. Dalloway; Woolf, Virginia; Film; Modernismus; proud vědomí; hodiny; Paní Dallowayová; Film